2018
DOI: 10.1186/s12871-018-0481-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, mitral valve disease, atrial fibrillation and low education level predict delirium and worst outcome after cardiac surgery in older adults

Abstract: BackgroundDelirium is a common complication after cardiac surgery in older adult patients. However, risk factors and the influence of delirium on patient outcomes are not well established. We aimed to determine the incidence, predisposing and triggering factors of delirium following cardiac surgery.MethodsOne hundred seventy-three consecutive patients aged ≥60 years were studied. Patients’ characteristics and two cognitive function assessment tests were recorded preoperatively. Perioperative variables were blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 41 publications
4
29
0
1
Order By: Relevance
“…Concordant with previous reports involving different patient cohorts, we identified hypertension, chronic pneumonitis, and renal insufficiency as further major predisposing risk factors for delirium in cancer patients (Oliveira et al, 2018). Cancer patients are at high risk for hypertension and chronic kidney disease, given that several cancer treatments cause hypertension or renal complications, like acute kidney injury or chronic kidney disease (Rosner and Perazella, 2017;Cohen et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Concordant with previous reports involving different patient cohorts, we identified hypertension, chronic pneumonitis, and renal insufficiency as further major predisposing risk factors for delirium in cancer patients (Oliveira et al, 2018). Cancer patients are at high risk for hypertension and chronic kidney disease, given that several cancer treatments cause hypertension or renal complications, like acute kidney injury or chronic kidney disease (Rosner and Perazella, 2017;Cohen et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…NfL levels of the other two CPB-DEL patients increased further until discharge. The notion of a high educational standard being protective in developing delirium is controversially discussed 27,28 . This association might either be based on a sufficient clearing mechanism for neurotoxic substances and debris detrimental for brain functioning 29 or a stronger constitution of the brain less sensitive to neurodegeneration 4 .…”
Section: Discussionmentioning
confidence: 99%
“…For publication bias, Begg's funnel plot suggested no significant bias (Figure 5(b)). Previous study showed that hypertension leading to microembolization phenomena and cerebral ischemia may be responsible for the occurrence of delirium [48].…”
Section: Discussionmentioning
confidence: 99%